The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1994
DOI: 10.1136/hrt.72.4.397
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous course of the left anterior descending coronary artery between the aorta and pulmonary trunk: a rare cause of myocardial ischaemia at rest.

Abstract: When the left anterior descending coronary artery follows an anomalous course between the aorta and pulmonary artery it can cause myocardial ischaemia or sudden death during exercise in young people. Coronary arteriography in a 27 year old man with angina pectoris at rest showed a left anterior descending coronary artery arising from a common right trunk and running from the aorta to the pulmonary artery. Follow up after revascularisation was uneventful.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 7 publications
(1 reference statement)
0
6
0
Order By: Relevance
“…This suggests that patients with interarterial type anomalous LAD may also have a high possibility of serious ischemic events. Raynord et al [5] reported one and Ono et al [11] two cases of interarterial type anomalous LAD with angina at rest, in which LIMA-to-LAD bypass were effective [5]. On the other hand, Mirchandani and Phoon [12] reported a 6-year-old with exertional chest pain.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…This suggests that patients with interarterial type anomalous LAD may also have a high possibility of serious ischemic events. Raynord et al [5] reported one and Ono et al [11] two cases of interarterial type anomalous LAD with angina at rest, in which LIMA-to-LAD bypass were effective [5]. On the other hand, Mirchandani and Phoon [12] reported a 6-year-old with exertional chest pain.…”
Section: Discussionmentioning
confidence: 96%
“…This particular course is angiographically identified in the right anterior oblique projection when the coronary artery forms a cranioposterior loop [3]. Interarterial course of left coronary artery causes serious risk to subject like angina, syncope, myocardial infarction and sudden cardiac death [4,5]. Atherosclerosis and life-threatening arrhythmias [6][7][8] or abnormal myocardial perfusion [9] could be seen in patients with CAA.…”
Section: Discussionmentioning
confidence: 98%
“…The angiographic pattern associated with this condition was unusual and in many views looked deceptively normal 5 . Roynard JL Cattan reported a case of origin of the left anterior descending artery arising from the common right trunk taking a course between aorta and pulmonary trunk and this could be a rare cause of myocardial ischemia at rest 6 . An isolated anomaly of the left anterior descending arising from the right sinus of valsalva is very rare.…”
Section: Discussionmentioning
confidence: 99%
“…It's course may be via anterior free wall, interarterial, retro-aortic or septal [9]. Interarterial course of left coronary artery causes serious risk to individual like angina, syncope, myocardial infarction and sudden cardiac death [9,10]. However, it is uncommon to have myocardial ischemia with septal course [11].…”
Section: Discussionmentioning
confidence: 97%